2019
DOI: 10.18203/2394-6040.ijcmph20190218
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of structured group reminiscence therapy in decreasing the feelings of loneliness, depressive symptoms and anxiety among inmates of a residential home for the elderly in Chittoor district

Abstract: Background: The proportion of the elderly population is increasing in low and middle-income countries. Apart from systemic illnesses, elderly people face mental illnesses. Effect of group reminiscence therapy in reducing some of the mental health aspects showing a promising effect but the evidence is lacking in Indian settings. The present study aimed to determine the effect of reminiscence therapy in decreasing the level of loneliness, depressive symptoms, and anxiety among the elderly population at an instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…However, studies of older people affected by psychiatric or neurologic pathologies lack representativeness and, therefore, do not allow for extrapolating their results to the general population of older adults. Longitudinal studies examining depression over time provided a variety of findings associated with reducing depression following treatment [50], oscillating between no effect and complete change of cognitive deficits [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of older people affected by psychiatric or neurologic pathologies lack representativeness and, therefore, do not allow for extrapolating their results to the general population of older adults. Longitudinal studies examining depression over time provided a variety of findings associated with reducing depression following treatment [50], oscillating between no effect and complete change of cognitive deficits [1].…”
Section: Introductionmentioning
confidence: 99%
“…This result was inconsistent with many reports. 24,31 To explain this finding, it can be said that most of the participants (88%) were illiterate and had to do manual and physical works such as agricultural and animal husbandry occupations to earn incomes, and therefore the physical chronic pain continues to increase with age. To reduce this contradictory issue, it might be better to provide suitable conditions and facilities such as non-invasive pain relief techniques and rational coping in nursing home centers.…”
Section: Discussionmentioning
confidence: 99%
“…Tarugu et al considered group reminiscence to improve the general health of older adults, living in nursing homes and believed that this method would recover the physical and social functions. 31 To explain this finding, reminiscence is usually a conceptual method for examining and reviewing life events and a psychological process, where past events and occasions are discussed. 14,26,30 Finally, the comparison of the overall scores of healthrelated QoL indicated that the evidence-based protocol for an 8-week group intervention could suggest beneficial values for participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses can implement the latter independently (Lin et al, 2003), allowing the elderly patient to review both good and bad experiences over their entire life and then develop more positive attitudes that may help them maintain good mental health. There is ample evidence that reminiscence therapy is an effective tool for reducing DS in the elderly (Pinquart & Forstmeier, 2012;Tarugu et al, 2019). Authors of a systematic review found that it was an effective nondrug intervention to alleviate depression in the elderly (Apostolo et al, 2016).…”
mentioning
confidence: 99%